Employee Resilience in A Private Educational Institution: Basis for An Enhanced And Sustainable Employee Wellness Plan - Eunice Mareth Querol Areola, PhD HSG; Pearliza Domalaon; Wednesdee-Perpetual A. Acasio; Evylou H. Bonquin; Jacob Michael d.L. Floresca; Maria Rita Pilar V. Ong (Journal of Sustainable Community Development (JSCD), 2023)
Academic institutions are said to be complex organizations that face a range of challenges and pressures which can result in higher stress levels among their human capital. The Pandemic that happened and the shifting back to the new normal poses’ different pressures and as an institution that promotes learning it is important to recognize these challenges and provide support and resources to promote sustained health and employee wellness. The main objective of this research was to identify the employees' resilience as measured in physical, occupational, and social well-being. Correlational analysis was used to establish relationships between responses to personal well-being and demographics of age, gender, and tenure. Findings revealed that participants’ well-being and participants’ responses exhibited significant, strong correlations in terms of designation, age, gender, and tenure in school. From these, recommendations for enhanced employee health and wellness were suggested and are aligned in the following areas: (i) performance; (ii) attitude; and (iii) mental health.